A Generalization of the «Lady-Tasting-Tea» Procedure to Link Qualitative and Quantitative Approaches in Psychiatric Research - Falissard, Bruno; Milman, Daniel; Cohen, David (International Journal of Statistics in Medical Research, 2013)
In Fisher’s “The Design of Experiments”, a trial was designed to test a lady’s claim to be able to discriminate whether the milk or the tea was added first to a cup. In this trial, eight cups are poured, four with milk first and four with tea first. They are then presented in random order to a subject who has to divide them into two sets of 4, according his/her belief about the "treatment" received. The present paper generalizes this design so that a hypothesis concerning the existence of two sub groups in a set of psychiatric patient records (whether written, audiotaped or videotaped) can be tested rigorously from a statistical point of view. Tables are proposed to enable power and sample size calculations. A real example is presented; it shows that psycho-dynamically oriented professionals are able to discriminate seven healthy adults who have experienced a sibling’s cancer during childhood or adolescence from seven matched controls. This method is particularly suited to small sample studies that explore elusive clinical hypotheses traditionally tackled with qualitative methodologies.